Observer la Terre pour appréhender spatialement les inégalités de santé : regard historique et prospectif sur l’utilisation de la télédétection dans le domaine de la santé - Vincent Herbreteau; Daouda Kassié; Emmanuel Roux; Renaud Marti; Thibault Catry; Artadji Attoumane; Christophe Révillion; Jérémy Commins; Nadine Dessay; Morgan Mangeas; Annelise Tran (Confins)
By providing a wide view of territories, satellite images and aerial photographs allow to capture the environmental factors that can affect the health of populations. Since the development of satellite remote sensing in the 1970s, its use in the health field has had moderate success. Although its potential was widely mentioned in the literature until the 2000s, its operational contribution was not obvious. It is only recently that health applications have been enriched and multiplied by the development of interdisciplinary approaches. This article aims to question the uses of remote sensing applied to health issues according to technical, historical, and thematic aspects in order to identify the bottlenecks. First, it offers a didactic view of theoretical principles, available data and possible uses. Through a bibliographic study, it offers a retrospective look at the evolution of its implementation in the field of health, which allows synthesizing current contributions: for operational mapping, for surveillance and analysis of the dynamics of infectious diseases or, to a lesser extent, to apprehend the vulnerabilities of populations such as difficulties in accessing healthcare. Finally, the article concludes on the limits, recommendations and perspectives for optimizing these uses, which are often constrained by technical and structural issues and for which methodologies still need to be developed.